Relação entre o controle postural e o risco de quedas de idosas obesas e não obesas - Costa, Janina Lied da (2021)
Given the population aging that directly impacts on epidemiological, social, economic, and environmental factors; it is clear the need to generate knowledge and improve the praxis in favor of prevention and health promotion of this population. One of the major risks offered to the health and quality of life of the elderly is the occurrence of falls, which can be associated with balance deficits, changes in postural control, and with the individual's high body mass index (BMI), among others. The following study aimed to investigate whether there is a relationship between postural control (PC) and the risk of falls (RF) in obese and non-obese elderly women. The following thesis is an arm of the integrated project entitled “Functionality, Risk of Falls, Level of Physical Activity and Postural Control in Women with and without Urinary Incontinence”. This is a descriptive, observational, cross-sectional survey with data already collected from elderly groups linked to Núcleo Integrado de Estudos e Atenção à Pessoa Idosa (NIEATI) of the Centro de Educação Física e Desportos (CEFD) of the Universidade Federal de Santa Maria (UFSM). The study has considered women aged 60 years or more evaluated to relationship the dynamic and static postural control variables and the body mass index of the elderly women participating in the research in relation to the risk of falls. The instruments used were: Registration Form prepared by the researchers, the Katz index to assess the level of independence in the practice of daily activities, the Mini Mental State Examination (MMSE) to assess cognitive status, anthropometric measures to calculate the index Body Mass and Waist Circumference, the Force Platform to assess dynamic and static CP. The Timed up and go (TUG) and Fall Risk tests were used to assess the RQ. The analysis of collected data was performed using descriptive statistics to characterize the sample, followed by the Shapiro-Wilk normality test for continuous variables. Two-tailed independent Student's T test for comparing parametric variables and the Mann-Whitney U test for non-parametric variables. For categorical variables, the Chi-square test followed by odds ratio and relative risk. For the association between BMI and Force Platform variables, the Pearson (parametric) and Spearman (non-parametric) correlation test. The level of significance was 0.05 and performed using the SPSS software version 17.0. The results showed that elderly women with obesity have a higher risk of falls when compared to non-obese women and, in the CP variables, random findings pointed to the interference of vision in the performance of the static test for obese elderly women and in the dynamic test (squat), the possible influence of muscle strength on the performance of non-obese elderly women. In conclusion, obesity and the reduction in muscle strength may characterize as potential risk to the occurrence of falls. It is essential then to be implemented actions that support and promote healthy habits to such population.